(untitled) (Clinics, 2013)
OBJECTIVE: Recent studies have shown that circulating microRNAs might be useful, novel biomarkers for the diagnosis of acute myocardial infarction. The aims of this study were to evaluate the expression of cardiac-specific miRNAs (miR-1, -133a, -208b, and -499) in patients with acute myocardial infarction and to compare the diagnostic values of these miRNAs with that of cardiac troponin T. METHODS: Sixty-seven plasma samples obtained from patients with acute myocardial infarction and 32 plasma specimens collected from healthy volunteers were analyzed in this study. The levels of cardiac-specific miRNAs (miR-1, -133a, -208b, and -499) were measured by quantitative reverse transcription-polymerase chain reaction, and the concentrations of plasma cardiac troponin T were measured using electrochemiluminescence-based methods and an Elecsys 2010 Immunoassay Analyzer. RESULTS: The levels of plasma miR-1, -133a, -208b, and -499 were significantly higher in acute myocardial infarction patients (all p